Assessment of Socio-Economic Sustainability in New European Union Members States in the years 2004-2012 - Michal Bernad Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
Implementation of a concept of sustainable development is currently considered as a dominant paradigm for plans and programs of economic policy at regional, national and international levels. It can be seen in the case of most significant documents that are used as the guidelines for strategic planning in the European Union such as a Europe 2020 plan. This implies the need for constant monitoring of the progress achieved in this area by the European Union countries with application of quantitative tools. The main objective of the research is to assess the progress achieved by the new member states in the field of implementing the concept of sustainability. The analysis is focused on the socio-economic sphere at a macroeconomic level in the years 2004, 2008 and 2012. In the analysis Eurostat data is used. Sustainable development should be treated as a multi-dimensional phenomena. As a result, a concept of taxonomic measure of development was applied here. This method, proposed by Zdzislaw Hellwig, is a useful tool for economic research. The main value of the Hellwig's proposals relates to its cognitive values in explaining economic reality, methodological simplicity and flexibility in its application. The tool can be used to analyze most of economic complex phenomena.
Keywords: Q01; C38; 330; Hellwig's method; pattern of development; multivariate analysis; taxonomy; Socio-Economic Sustainable Development